Spin-orbit torque switching of chiral magnetization across a synthetic antiferromagnet - Kang Wang (Nature Portfolio, 2021)
Exchange interactions between spins in a magnetic system can be engineered using magnetic multilayer systems in order to investigate a rich variety of magnetic phenomenon. Here the authors investigate the nature and control of magnetization of a synthetic antiferromagnetic stack with built in planar asymmetry and find evidence of an asymmetric current-driven switching in the chiral magnetization across the magnetic multilayers.